2023
DOI: 10.1002/ctm2.1167
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranyl diphosphate synthase: Role in human health, disease and potential therapeutic target

Abstract: Geranylgeranyl diphosphate synthase (GGDPS), an enzyme in the isoprenoid biosynthesis pathway, is responsible for the production of geranylgeranyl pyrophosphate (GGPP). GGPP serves as a substrate for the post‐translational modification (geranylgeranylation) of proteins, including those belonging to the Ras superfamily of small GTPases. These proteins play key roles in signalling pathways, cytoskeletal regulation and intracellular transport, and in the absence of the prenylation modification, cannot properly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 252 publications
(565 reference statements)
0
9
0
Order By: Relevance
“…GGPS1 monomers associate into a trimer of dimers, forming a hexamer (Figure 1i). In certain circumstances, an octamer can also form (Kavanagh et al, 2006;Muehlebach & Holstein, 2023). GGPP binds to a mostly hydrophobic GGPS1 pocked formed by residues R28, L31, F35, H57, R73, L122, L155, F156, Al159, V160, and F184 (Consortium PD-K., 2020;Kavanagh et al, 2006) (Figure 1i).…”
Section: Structural Analysis and Predicted Effectmentioning
confidence: 99%
“…GGPS1 monomers associate into a trimer of dimers, forming a hexamer (Figure 1i). In certain circumstances, an octamer can also form (Kavanagh et al, 2006;Muehlebach & Holstein, 2023). GGPP binds to a mostly hydrophobic GGPS1 pocked formed by residues R28, L31, F35, H57, R73, L122, L155, F156, Al159, V160, and F184 (Consortium PD-K., 2020;Kavanagh et al, 2006) (Figure 1i).…”
Section: Structural Analysis and Predicted Effectmentioning
confidence: 99%
“…GGPPSs also serve as precursors of biosynthesis of a diverse class of specialized terpenoids such as polyterpenes, polyprenols, tocopherols, gibberellins, abscisic acid, strigolactones, phytyl esters, and plastoquinones (Akhtar et al, 2017; Tholl and Lee, 2011). Previously, GGPPSs have been functional characterized in plants, bacteria, yeast and mammals, but the roles of GGPPS in insect species has been scarcely understood so far (Barja & Rodriguez‐Concepcion, 2021; Muehlebach & Holstein, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…GGPP serves as a fundamental precursor of various primary and secondary metabolites, including terpenoids, gibberellins, carotenoids, and chlorophyll, in plants. Additionally, GGPP therapies [6,7]. GGPPS genes have been the subject of extensive research in plan have reported that mutations in GGPPS genes can result in seed albinism in Zhou et al (2021) conducted a study in rice and found that the recruitment GGPPS controls the metabolism of chlorophyll biosynthesis [9].…”
Section: Introductionmentioning
confidence: 99%